Netnography Study of Menjadi Manusia Community Network Communication on Discord - Chelsea Amanda Putri; Monica Christiana Prajugo; Sherlynn Yuwono; Edward Hiroshi Tandawidjaja; Ivan Christian Harijono (Journal of Content and Engagement, 2023)
Mental health issues have been widely discussed in this modern era. By doing so, mental health care communities have been increasingly developed globally. One of the most popular social communities in Indonesia is Menjadi Manusia. This community has gained a large number of members across different social media platforms, including Discord as their communication network. This research was conducted using digital netnography method to see communication patterns of Menjadi Manusia community network on Discord. The community targeted in this study consists of all Discord users that actively participate in discussions in the Menjadi Manusia community. Using the netnography method, this research observed conversations and messages in Discord, as a safe place to talk, speak and share their stories or problems freely and to be human through the discord community channel. Through this channel, there are places where people can speak up specifically through communication disclosure. These interactions are made to fulfil the needs and purpose of this community, to be a safe place to fix their mental health and cure every emotion and problem they have to each other.